Pin Up Style dalam Fotografi Fashion Kontemporer - Tiara Sekar Adhitia; M. Kholid Arif Rozaq; M. Fajar Apriyanto (Specta: Journal of Photography, Arts, and Media, 2019)
Fashion becomes a social symbol that gives the cultural identity to a person. Pin up style has existed since the late 1950s. This style which is a combination of urban style and pop culture is identical with a light, tight, and semi-open dress. The image sticking on pin up style fashion makes the women called as "teasing ladies". The chosen genre is contemporary fashion photography that is a genre in photography which aims to show the clothes and other fashion items influenced by the impact of modernization.The result of this final assignment project is a series of fashion photography which uses the fashion style of 1950s that is pin up style. In every visualization of the creation of this photographic work, it aims to present the story based on the ideas and the concepts as well as to introduce the type of pin up style for each photograph. The background, the property, the make up, the hair style, as well as the surrounding objects are used to support the story in the resulted photographs. Keywords: pin up style, fashion, contemporary fashion photography